Learning Using TikTok for Reducing Pronunciation Errors - Khikmah, Silvia Lailatul; Wijaya, Armeria; Ro’ifah, Ro’ifah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Technology has advanced swiftly within the realm of education, and it has had a significant impact on teaching and learning. The researcher uses a social media TikTok duet feature, which is currently very popular among students as a medium for English learning. These studies specifically focus on the potential of TikTok for reducing pronunciation errors. The aim of this research is to reduce students' pronunciation errors by using the TikTok application. The problem that will be examined is whether TikTok can reduce students' pronunciation errors. This research employed a quantitative methodology and adopted an experimental design. The participants were segregated into two categories: an experimental group and a control group. The study sample was derived from two classes at SMP Negeri 1 Pandaan, specifically the 9th grade, comprising a total of 62 students. The instruments used were pretest and posttest administered before and after treatment. The examination test comprised of typically dispersed understudies with comparable attributes, guaranteeing homogeneity. Factual procedures, for example, free examples t-test and estimated time of arrival squared test were utilized for examination. The SPSS test yielded a value of 0 that was statistically significant. 000. As 0.000 under 005. Consequently, H0 is dismissed and H1 is acknowledged. This study saw as a higher η-square worth (0.733) in the exploratory gathering contrasted with the benchmark group (0.582), showing a bigger impact size because of exploratory condition. This demonstrates that roughly 73. The treatment was responsible for 3% of the experimental group's variance in the dependent variable. It showed that students reduce after using TikTok as a learning media because TikTok is popular social media. So that student can be motivated to learning material. This implies that using TikTok application as a learning media can reduce pronunciation errors in students.